Professional ASP.NET 4.5 in C# and VB - Jason N. Gaylord
ASP.NET is Microsoft's technology for building dynamically generated web pages from database content. Originally introduced in 2002, ASP.NET has undergone many changes in multiple versions and iterations as developers have gained a decade of experience with this popular technology. With that decade of experience, this edition of the book presents a fresh, new overhauled approach